Corporate Bond Market Transaction Costs and Transparency - EDWARDS, AMY K.; HARRIS, LAWRENCE E.; PIWOWAR, MICHAEL S. (Journal of Finance, 2007)
ABSTRACT Using a complete record of U.S. over‐the‐counter (OTC) secondary trades in corporate bonds, we estimate average transaction costs as a function of trade size for each bond that traded more than nine times between January 2003 and January 2005. We find that transaction costs decrease significantly with trade size. Highly rated bonds, recently issued bonds, and bonds close to maturity have lower transaction costs than do other bonds. Costs are lower for bonds with transparent trade prices, and they drop when the TRACE system starts to publicly disseminate their prices. The results suggest that public traders benefit significantly from price transparency.